Thermo-compression of biodegradable thermoplastic corn starch films containing chitin and chitosan - Lopez, Olivia Valeria (2014)
Films based on thermoplastic corn starch (TPS) and chitosan/chitin were obtained by melt-mixing and thermo-compression. Chitosan and chitin incorporation to TPS matrix induced some structural modifications due mainly to the interactions between starch hydroxyl and chitosan/chitin amino groups. Crystallinity degree of TPS films was increased with biopolymers incorporation. Enthalpy melting values for TPSechitosan/chitin films resulted lower than those corresponding to TPS control ones. Films had homogeneous and smooth surfaces, without pores and cracks and no glycerol migration was evidenced by Scanning Electronic Microscopy. Films fracture surfaces were uniform without the presence of unmelting starch granules neither chitosan/chitin agglomerates. Films with chitosan/chitin presented higher color, UV absorption capacity and opacity than TPS films. Addition of 10 g chitosan or chitin/100 g starch decreased 35 and 56% water vapor permeability, respectively. Biopolymers addition to TPS increased tensile strength and elastic modulus, and decreased elongation at break. Starch and glycerol rich domains where evidenced in TPS matrixes by Dynamic Mechanical Analysis. Finally, TPS-chitosan films reduced Staphylococcus aureus and Escherichia coli growth in the contact zone.